The Toyota Way: 14 Management Principles from the World's Greatest Man ufacturer - Liker, Jeffrey K. (McGraw-Hill, 2004)
How to speed up business processes, improve quality, and cut costs in any industryIn factories around the world, Toyota consistently makes t he highest-quality cars with the fewest defects of any competing manuf acturer, while using fewer man-hours, less on-hand inventory, and half the floor space of its competitors. The Toyota Way is the first book for a general audience that explains the management principles and bus iness philosophy behind Toyota's worldwide reputation for quality and reliability.Complete with profiles of organizations that have successf ully adopted Toyota's principles, this book shows managers in every in dustry how to improve business processes by:Eliminating wasted time an d resources Building quality into workplace systems Finding low-cost b ut reliable alternatives to expensive new technology Producing in smal l quantities Turning every employee into a quality control inspector